Colloidal synthesis and magnetic properties of anisotropic-shaped spinel CuCr2Se4 nanocrystals. Issue 50 (16th June 2017) - Pang, Chao; Yang, Ruiqiang; Singh, Amit; Chen, Hanjiao; Bowman, Michael K.; Bao, Ningzhong; Shen, Liming; Gupta, Arunava
Abstract : Anisotropic-shaped CuCr2 Se4 nanocrystals have been synthesized by thermal decomposition and reaction of novel mixed metal–oleate complexes with selenium in a high-boiling point organic solvent, trioctylamine. Abstract : Anisotropic-shaped CuCr2 Se4 nanocrystals have been synthesized by thermal decomposition and reaction of novel mixed metal–oleate complexes with selenium in a high-boiling point organic solvent, trioctylamine (TOA). The synthesized CuCr2 Se4 nanocrystals exhibit close to triangular and hexagonal morphology, with an average size of 20 nm. X-ray diffraction patterns and XPS spectral analysis confirm the formation of the pure spinel phase without any impurities. A possible reaction mechanism is suggested and formation pathways for the triangular and hexagonal shaped CuCr2 Se4 nanocrystals are proposed. Magnetic studies indicate that the anisotropic-shaped CuCr2 Se4 nanocrystals are superparamagnetic near room temperature but exhibit ferromagnetic behavior at lower temperatures, with magnetization values of 31 and 43 emu g −1 at 300 and 5 K, respectively.